Long-term nutritional status after total gastrectomy was comparable to proximal gastrectomy but with much less reflux esophagitis and anastomotic stenosis - Ding, Shikang; Zheng, Xiaohao; Wang, Shenghui; Wu, Ming; Wu, Yunzi; Sun, Chunyang; Yang, Lin; Xue, Liyan; Wang, Bingzhi; Wang, Chengfeng; Xie, Yibin (Frontiers in Oncology, 2022)
Aim To compare the long-term nutritional status, reflux esophagitis and anastomotic stenosis, between total gastrectomy (TG) and proximal gastrectomy (PG). Methods Patients who underwent PG or TG in this single institution between January 2014 and December 2016 were included in this study. The inclusion and exclusion criteria were defined. One-to-one propensity score matching (PSM) by the demographic and pathological characteristics was performed to compare the long-term outcomes between the two groups. The primary endpoint was long-term nutritional status, and the second endpoints were reflux esophagitis and anastomotic stenosis. Long-term nutritional status was valued by percentage of body mass index (%BMI), body weight, and blood test including total protein, prealbumin, hemoglobin and total leukocytes. Results Totally 460 patients received PG or TG in our institution for the treatment between January 2014 and December 2016 and according to the inclusion and exclusion criteria 226 cases were included in this study finally. There was no significant difference as to nutritional status in the end of first 5 years after PG or TG. While reflux esophagitis and anastomotic stenosis were significantly higher in the PG group than in the TG group (54.4% versus 26.8%, p < 0.001; 14.9% versus 4.5%, p=0.015; respectively). Overall survival rates were similar between the two groups after PSM (5-year survival rates: 65.4% versus 61.5% in the PG and TG groups, respectively; p = 0.54). The rate of carcinoma of remnant stomach after PG was 3.5% in this group of patients. Conclusions TG should be more aggressively recommended for the similar nutritional status, significantly lower reflux esophagitis and anastomotic stenosis, and free of carcinoma of remnant stomach compared with PG.